2019
DOI: 10.1136/bmjsem-2018-000501
|View full text |Cite
|
Sign up to set email alerts
|

Is a low Functional Movement Screen score (≤14/21) associated with injuries in sport? A systematic review and meta-analysis

Abstract: ObjectiveTo assess whether Functional Movement Screen (FMS) score is associated with subsequent injuries in healthy sportspeople.DesignSystematic review and meta-analysis.Data sourcesThe following electronic databases were searched to December 2017: Medline, PubMed, PsycINFO, SPORTDiscus, Cumulative Index of Nursing and Allied Health Literature, Scopus, Embase, and Physiotherapy Evidence Database.Eligibility criteria for selecting studiesEligibility criteria included (1) prospective cohort studies that examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
1
23
0
2
Order By: Relevance
“…A lower FMS score is associated with an elevated injury risk [15]. We found that Wushu athletes who had FMS score less than 16 (sensitivity = 80%, specificity = 56%) had a higher odd of having some injury history (OR = 5.096), than those who had score over 16.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…A lower FMS score is associated with an elevated injury risk [15]. We found that Wushu athletes who had FMS score less than 16 (sensitivity = 80%, specificity = 56%) had a higher odd of having some injury history (OR = 5.096), than those who had score over 16.…”
Section: Discussionmentioning
confidence: 69%
“…It should be noted that future studies need to consider the potential threshold scores for functional tests. Moreover, prospective studies that include detailed injury surveillance and a more robust injury definition are needed, in order to compare results across different studies [15]. While FMS can be used as a measuring tool and method to predict sports injury for Wushu athletes, the score of FMS test is limited to relate to the incidence of sports injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Functional Movement Screen (FMS)™ is a screening tool used to evaluate mobility, balance, and postural stability using seven fundamental movement patterns and three additional clearing tests ( Cook et al., 2014 ; Scudamore et al, 2019 ; Cook, Burton & Hoogenboom, 2006a ; Cook, Burton & Hoogenboom, 2006b ). Acceptable results for the intra- and interclass reliability (coefficients of 0.869 and 0.843, respectively) of the total FMS score (TFMS), calculated using the sum of the seven movement scores ( Scudamore et al, 2019 ; Moran et al, 2017 ; Trinidad-Fernandez, Gonzalez-Sanchez & Cuesta-Vargas, 2019 ; Bonazza et al, 2017 ; Moore et al, 2019 ), have been reported ( Cuchna, Hoch & Hoch, 2016 ; Moran et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies pertaining to FMS™ and sports injuries of athletes considered the total scores and asymmetry of the FMS™ to be more useful for evaluating the injury risk of older athletes ( Moore et al., 2019 ). Another review reported that the relationship between the FMS™ score and injury is unclear as the heterogeneity of the study populations (type of athletes, age, and sport exposure) and the definition of injury used in the studies made it difficult to draw definitive conclusions ( Trinidad-Fernandez, Gonzalez-Sanchez & Cuesta-Vargas, 2019 ). Therefore, there is no clear conclusion about the relationship between FMS™ and sports injuries.…”
Section: Introductionmentioning
confidence: 99%